Does income inequality really matter for credit booms?. (19th November 2022) - Ayadi, Rym; Naceur, Sami B.; Challita, Sandra
Abstract: This paper addresses the question whether income inequality is associated with credit booms, alongside other macroeconomic factors. We distinguish between the different types of credit booms—real estate credit booms, household credit booms, firm credit booms and credit booms that turn into crises. Furthermore, our analysis of a sample of 70 countries between 1990 and 2016 does not provide any evidence of credit booms driving income inequality. We observe that capital inflows increase the likelihood of credit boom occurrence, while countries experiencing high economic growth tend to have more credit booms. Finally, we note that credit booms are more frequent in countries with fixed exchange rate regimes.